Proceedings of the 8th Pacific Rim International Conference on Advanced Materials and Processing (PRICM-8) - Marquis, FernD.S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
PRICM-8 features the most prominent and largest-scale interactions in advanced materials and processing in the Pacific Rim region. The conference is unique in its intrinsic nature and architecture which crosses many traditional discipline and cultural boundaries. This is a comprehensive collection of papers from the 15 symposia presented at this event.
Keywords: Materials -- Analysis; Mechanical engineering; Materials; Characterization and Analytical Technique; Mechanical Engineering; Materials Engineering